Nuclear receptors rock around the clock. (15th April 2014) - Zhao, Xuan; Cho, Han; Yu, Ruth T; Atkins, Annette R; Downes, Michael; Evans, Ronald M
Abstract Circadian rhythms characterize almost every aspect of human physiology, endocrinology, xenobiotic detoxification, cell growth, and behavior. Modern lifestyles that disrupt our normal circadian rhythms are increasingly thought to contribute to various disease conditions ranging from depression and metabolic disorders to cancer. This self‐sustained time‐keeping system is generated and maintained by an endogenous molecular machine, the circadian clock, which is a transcriptional mechanism composed of the transcription factors CLOCK and BMAL and their co‐repressors, PER and CRY. Nuclear receptors (NRs) represent a large family of hormone‐sensitive transcriptional regulators involved in a myriad of biological processes such as development, energy metabolism, reproduction, inflammation, and tissue homeostasis. Recent studies point not only to NR regulation by the clock, but also to NR regulation of the clock itself. Here, we discuss recent studies that functionally and mechanistically implicate NRs as key components of both the universal and adaptive circadian clock mechanisms. As proven pharmacological targets, nuclear receptors are promising targets for therapeutic control of many pathological conditions associated with the disruption of circadian rhythm.